CRITERIA AND INICES OF EDUCATION QUALITY MONITORING IN UKRAINIAN AND EUROPEAN UNIVERSITIES - E. V. Podkopayeva (Russian State Vocational Pedagogical University, 2015)
The paper looks at the issue of quality monitoring of higher education. The research is aimed at identifying the criteria and indices related to educational activities of Ukrainian universities, and required for establishing a unified and scientifically proved estimation system. As the Ukraine strives for integration into the European educational environment, the author analyzes the recognized scientific recourses concerning the education quality assessment such as the models of educational indicators of UNESCO, the European Union and Organization for Economic Cooperation and Development, as well as the documents and recommendations of the European Association for Quality Assurance in Higher Education (ENQA).The author singles out the following estimation criteria: competence, independence, utility, accuracy, feasibility of recommendations for quality assurance, transparency of monitoring procedures and  compliance with the laws and moral norms. The given indices of education quality monitoring are based on the systematic approach and incorporate the indicators of provision, effectiveness and impact; therefore, the education quality can be analyzed as the process, management system and outcomes of the process. The above three groups of indicators form the effective instruments for education quality assessment corresponding with the world educational standards.